Mission Nuestra Senora de La Soledad - Hubert A. Lowman::::::photographer::: (H. S. Crocker Company, Inc.)
Back of postcard reads: 'Founded 1791, near Soledad, California. For years seldom visited except by the rain, wind and fog, only pitiful rows of ruined adobe walls remained at Soledad. But now the chapel, seen through an old doorway, is rebuilt... and thus work begins on this, the last mission in the chain of 21 to be restored.' An official California Mission Trails Association card.